E-Wave software: EBSD-based dynamic wave propagation model for studying seismic anisotropy. (September 2018) - Zhong, Xin; Frehner, Marcel
Abstract: The study of seismic anisotropy has benefited from the wide application of the electron backscatter diffraction (EBSD) technique that provides complete information on the crystallographic and shape preferred orientations in 2D sections. Classical effective medium theory statistically approximates the seismic anisotropy based on the crystallographic preferred orientation, but the shape preferred orientation is often idealized as e.g. parallel layering or oriented inclusions. Due to higher demands in precisely quantifying seismic anisotropy in natural rocks and taking full advantage of the EBSD technique, dynamic wave propagation methods have received broad attention. This paper presents the MATLAB program E -Wave based on a novel approach to directly use EBSD data for 2D numerical wave propagation simulation. The complete mechanical formulation and numerical benchmarks with simple model setups are presented. The E -Wave program allows straightforward EBSD data import, finite-difference simulations with one-button click, and automatic result analysis. The E -Wave program can be a helpful and independent tool in future works to shed light on the relationship between microstructures and seismic anisotropy, and contribute from the modelling perspective to studies in seismology, geodynamics and rock physics. Highlights: E -Wave program is provided to perform dynamic wave propagation model. Effects of SPO and CPO can be separated using E -Wave program. Effects of elastic scattering and frequency influence on seismic anisotropy can be studied.